Effect of centrally acting drugs on the uptake of γ-aminobutyric acid (GABA) by slices of rat cerebral cortex - Harris, M. (1973)
1. The effects of centrally acting drugs on the uptake of (3)H-γ-aminobutyric acid (GABA) by slices of rat cerebral cortex have been studied. 2. Many centrally acting drugs at concentrations of 0·1-1·0 mM significantly inhibited the uptake of (3)H-GABA by cortical slices, but the only classes of drugs in which all members consistently produced inhibition of uptake were the phenothiazines, tricyclic antidepressants, and butyrophenones. 3. The receptor blocking drugs; phentolamine, propranolol, thymoxamine, mepyramine, and diphenhydramine at concentrations of 0·5-1 mM also significantly reduced the uptake of (3)H-GABA. However, atropine, hexamethonium and (+)-tubocurarine had little effect on the uptake of (3)H-GABA by cortical slices. 4. Centrally acting drugs, which did not significantly inhibit (3)H-GABA uptake, included barbiturates, local anaesthetics, hallucinogens, monoamine oxidase inhibitors, anticonvulsants, and convulsants (except picrotoxin). 5. Chlorpromazine, prochlorperazine, L-2,4,diaminobutyric acid, desmethylimipramine, and iprindole inhibited the uptake of (3)H-GABA by 50% (IC50) at concentrations of 30-100 μM. The most potent inhibitor of (3)H-GABA uptake was p-chloromercuriphenylsulphonate (IC50 = 18 μM). 6. With the exception of L-2,4,diaminobutyric acid, an outstanding characteristic of these drugs was their complete lack of specificity. Thus at the IC50 for GABA, p-chloromercuriphenylsulphonate, chlorpromazine, prochlorperazine, iprindole, desmethylimipramine, apomorphine and diphenylhydramine also inhibited the uptake of radioactive glycine, alanine, noradrenaline, and 5-hydroxytryptamine. The uptake of the latter two compounds was often inhibited to a greater extent than GABA, glycine and alanine. 7. Kinetic analysis indicated that the inhibition of (3)H-GABA by p-chloromercuriphenylsulphonate, chlorpromazine, and desmethylimipramine was noncompetitive. L-2,4,Diaminobutyric acid reduced the uptake of (3)H-GABA by a `mixed' type of inhibition. 8. The present results do not support the suggestion that some centrally acting drugs may produce their effects by reducing the uptake of GABA in the brain after its release from inhibitory nerve terminals. Conceivably, the design of compounds which interfere effectively with the mechanisms of GABA operated synapses may lead to the introduction of whole new groups of centrally acting drugs.